Akupresur Mengurangi Mual dan Muntah Pada Anak Yang Menjalani Kemoterapi - IGA Dewi Purnamawati (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2018)
Cancer patients assess nausea is the most unpleasant side effect of chemotherapy, although the provision of antiemetic therapy has been given intensively. Nearly 70% of adult patients and 58% of school-age children and adolescents receive highly emetogenic chemotherapy agents, as a result of which patients complain of nausea (Ryan, 2010). Acupressure is one of the alternatives to effective interventions to reduce complaints of nausea and vomiting. Acupressure is also a non-invasive intervention and is relatively difficult to do (Lee & Frazier, 2011). This EBN application aims to achieve quality nursing care through comprehensive nursing interventions and improve nursing services that pay attention to the principles of atraic care in children undergoing chemotherapy by minimizing complaints of nausea and vomiting. Research methods with systematic reviews. The result of this EBN application is the effectiveness of acupressure in reducing nausea and vomiting in children undergoing chemotherapy.